ACTION FOR DECLARING THE ABUSIVE CHARACTER AND FOR ASCERTAINING THE ABSOLUTE NULLITY OF SOME CLAUSES FROM A CREDIT CONTRACT CONCLUDED BETWEEN A PROFESSIONAL MERCHANT AND A CONSUMER. CONDITIONS OF ADMISSIBILITY FROM THE PERSPECTIVE OF THE SPECIAL LAW AND OF THE COMMON LAW. EFFECTS ON THE DEVELOPMENT OF THE CONTRACT - Eugenia VOICHECI (Challenges of the Knowledge Society, 2018)
The Council Directive 93/13/EEC on unfair terms in consumer contracts was transposed into the Romanian legislation under the Law no. 193/2000 on unfair terms in the agreements concluded by professionals and consumers. The above legislation sets the legal framework of consumer protection, defines both the consumer and professional and establishes the conditions to be cumulatively met in order for a term to be declared unfair. The above-mentioned legislation does not institute a juris et de jure presumption regarding the unfairness of the terms listed in the annex, therefore the supervisory body and courts of law are called upon to assess in each case subjected to control whether a certain term is unfair or not. The Council Directive 93/13/EEC and the Law no. 193/2000 do not impose, exhaustive definitionsforthe professional and the consumer status and do not exclude the incidence of other provisions of internal law, either lex specialis or lex generalis, for determining such status. The above-mentioned legislation does not exclude the possibility to invoke other grounds for nullity specified in other lex specialis or in lex generalis in a trial for ascertaining the unfairness of the terms and the nullity of certain clauses. Thus, an analysis of the specific jurisprudence reveals a juxtaposition of distinctive legal grounds. Not lastly, the above-mentioned legislation does not expressly provide whether the courts of law are competent to modify a term which was declared unfair, nor does it provide the circumstances under which an agreement could be executed after the elimination of the unfair term. The above-mentioned legislation provide in terminis solely the incumbent nature of the consumer’s agreement for the continuation of the contractual relationship. In this context, the relevant materials for finding solutions which could lead to safeguarding the agreement are the C.J.E.U. case-law and the Romanian law.